A Secret Demand: On Endless Forms of Fiction in Borges’ "El milagro secreto" - Chambers, Adam (Elephant & Castle, 2019)
To gain a deeper understanding of Jorge Luis Borges’ philosophy of literature, we will closely examine his short story, El milagro secreto (The Secret Miracle), a strange and often overlooked writing, from paradoxically, his most famous collection, Ficciones (1944). As I will attempt to demonstrate, the story is unique in Borges’ œuvre, in that it deals specifically with the subject of secrets as an allegory to help understand the critical value of literature. In more detail, through a close reading of the story, and in dialogue with the literary theories of Maurice Blanchot and Michel Foucault, I hope to demonstrate how Borges’ fictions produce secrets, which although never fully answered, open up forms of both possibility and pleasure.